Synthesis and optical spectroscopy of Na3Y(VO4)2:Eu3+ phosphors for thermometry and display applications. Issue 12 (8th March 2022) - Kachou, Ikhlas; Saidi, Kamel; Salhi, Rached; Dammak, Mohamed
Abstract : A new NYVO:Eu 3+ phosphor was prepared using the sol–gel method and its exhibits high-brightness and thermally stable emission that could be used for display and temperature sensing applications. Abstract : A new Na3 Y(VO4 )2 :Eu 3+ (NYVO:Eu 3+ ) phosphor was prepared using the sol–gel method. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to evaluate phase purity and particle size, respectively. The optical properties were investigated by UV-visible absorption, PL, and PLE spectroscopies. The absorption measurements show the formation of the vanadate host by the presence of its characteristic band in the visible region related to VO4 3− groups. The experimental results show that the NYVO:Eu 3+ phosphors exhibit high-brightness and thermally stable emission. Under near-ultraviolet (UV) excitation, both the broadband emission from VO4 3− groups and the sharp peak emissions from Eu 3+ ions are observed. The highest luminescence intensity was achieved for an optimal europium concentration of 15 mol%. The study of the chromaticity parameters of these compounds gives a thermally stable hot emission in the red domain, with a color purity of about 85%, which qualifies the NYVO:Eu 3+ compound as a potential phosphor for light-emitting diode (LED) applications. Thermal sensing using NYVO:Eu 3+ phosphors are based on monitoring the luminescence intensity ratio between the NYVO host emission and Eu 3+ luminescence lines. Notably, the optical thermometry of NYVO:Eu 3+ was characterized based on the fluorescence intensity ratio of VO4 3− and Eu 3+ emissions in the 298–440 K range, with maximum absolute and relative sensitivities of 3.4% K −1 and 0.0032 K −1 respectively and a temperature uncertainty of 0.01. NYVO:Eu 3+ can then be considered as a potential red phosphor for application in ultraviolet-pumped white light-emitting diodes and as a potential optical thermometer. It provides new possibilities for the design of multifunctional materials for red light-emitting diodes and for non-contact thermometry.